Mechanism of the hypotensive action of methyldopa in normal and immunosympathectomized rats - Ayitey-Smith, E. (1970)
1. The antihypertensive action of methyldopa was investigated in the light of the prevailing false sympathetic neurotransmitter hypothesis of Day & Rand (1963). Immunosympathectomized and normal animals were used for the investigation. 2. Methyldopa in a single injection significantly decreased the blood pressure in control hypertensive, immunosympathectomized normotensive, and normal rats. Guanethidine did not decrease the blood pressure of immunosympathectomized rats; it decreased the blood pressure of control and control hypertensive rats. 3. The hypotensive effect of methyldopa was not antagonized by adrenoceptor and ganglion blocking agents or by the inhibition of dopamine β-oxidase. 4. High doses of methyldopa produced less hypotension than relatively low doses. This might be due to an antagonism of the hypotensive effect by methylnoradrenaline, which is formed from methyldopa. 5. The antihypertensive action of methyldopa could not be correlated with any change in aortic sodium or potassium. 6. It is concluded that methyldopa does not exert its hypotensive effect by producing a weakly active false sympathetic neurotransmitter.